Inhibition of inflammatory cell infiltration by antagonistic peptides that specifically bind to CCR5 via regulation of the NF-kB signaling pathway in rats with colitis - Yang-Da Song; Yi-Hang Song; Si-Xue Liu; Hua-Rong Huang; Ying-Qiang Zhong (Archives of Medical Science)
Introduction CC chemokine receptor 5 (CCR5) and the NF-kB signaling pathway play important roles in the pathophysiology of inflammatory bowel disease (IBD). Previously, we synthesized two peptides (GH and HY peptides) that specifically bind to the first and the second extracellular loops (ECL1 and ECL2, respectively) of CCR5 and preliminarily found an inhibitory effect of these peptides on colitis. However, the specific mechanism by which these two peptides regulate trinitrobenzene sulfonic acid (TNBS)-induced colitis in rats remains unclear. Aim of the study was to further investigate the effect and mechanism of CCR5 binding peptides in rat colitis.